Tenda dos milagres em (dois) tempos de autoritarismo: as marcas da intolerância nas narrativas de Jorge Amado e Nelson Pereira dos Santos - Cabreira, Luciane Farias (2014)
This dissertation examines comparatively the Tenda dos milagres novel, written by Jorge Amado in 1969, and its filmic transposition, of the same title, directed by Nelson Pereira dos Santos in 1977. Discusses relations between literary text and the filmic text, presenting the analysis of narrative texts and reporting the result of the literature review of theoretical-critical support and the consolidation of filmic and literary corpus, considered the respective contexts in which the works were created and circulated. The theoretical amount mobilized for the completion of the critical reading of texts of fiction was selected between literary theories and movie, among them those of intertextuality, transcreation, the adaptation and the metalanguage, which enabled the comparative reflection. In a second moment, the text presents the comparative analysis itself between book and movie, based on the historical context of its elaboration and reception, marked by intolerance and repression, religious, social, cultural political and ethnic, brands from time of authoritarianism and institutionalized violence during the period of the civil-military dictatorship of 1964 post-coup Brazilian. In this context, the research examines the hypothesis that presides over the investigation, centered on the filmmaker's action, which, by means of the filmic language, Advancer-and-Turner reading for the apparent literary, showing the context of intolerance observed in history conveyed in book, but also questioning historical issues, recurrent in the formation of society and supporting the Brazilian cultural imagery. It is in this framework that the contrastive reading seeks to contribute to the study of the critical reception of the two works, read in conjunction and under the comparative bias.